Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding - Oliver, Paul M.; Richards, Stephen J.; Donnellan, Stephen C. (Zootaxa, 2019)
New Guinea is home to the world’s most diverse insular frog biota, but only a small number of taxa have been included in genetically informed assessments of species diversity. Here we describe two new species of New Guinea treefrog in the genus Litoria that were first flagged during assessments of genetic diversity (DNA barcoding) and are currently only known from the holotypes. Litoria pterodactyla sp. nov. is a large green species in the Litoria graminea species complex from hill forests in Western Province, Papua New Guinea and is the third member of this group known from south of the Central Cordillera. Litoria vivissimia sp. nov. is a small, spike-nosed species from mid-montane forests on the Central Cordillera. It is morphologically very similar to Litoria pronimia, but occurs nearly 1000 m higher than any known locality for that species. More extensive genetically informed assessment of diversity in New Guinea frogs seems certain to reveal many more as-yet-unrecognised taxa in complexes of morphologically similar species.